Laminated film and image display device
The laminated film with a decorative, low, and high refractive index layers addresses the issues of brightness and color unevenness in conventional decorative films, resulting in improved design quality and commercial value for image display devices.
Patent Information
- Application Number
- JP2023094954
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-08
- Publication Date
- 2024-12-19
AI Technical Summary
Conventional decorative films for image display devices suffer from insufficient brightness and uneven coloration, which detract from their commercial value.
A laminated film with a decorative layer having an uneven structure, a low refractive index layer with a refractive index of 1.30 or less and a thickness of 0.3 μm or more, and a high refractive index layer with a refractive index of 1.60 to 2.20 and a thickness of 0.3 μm or more, designed to enhance brightness and suppress color unevenness.
The laminated film achieves high brightness and suppressed color unevenness, enhancing the design quality and commercial value of image display devices.
Smart Images

Figure 2024176430000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate film and an image display device. [Background technology]
[0002] Decorative films are used as a means for improving the design of various products. For example, a technique has been proposed in which a decorative film is attached to a cover case for housing a smartphone, a tablet terminal, or the like and / or a glass panel constituting the back surface (a surface not involved in image display) of an image display device, thereby imparting design to the image display device itself. For example, a decorative film having a concave-convex layer and a low refractive index layer is known. However, with conventional decorative films, problems may arise such as insufficient brightness of the applied design and / or color unevenness in the applied design. Therefore, a decorative film capable of further increasing the commercial value of an image display device is desired. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2022-57471 [Patent Document 2] JP 2017-47594 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention has been made to solve the above-mentioned conventional problems, and its main object is to provide a laminated film that can realize a design having high brightness and suppressed color unevenness. [Means for solving the problem]
[0005] [1] A laminate film according to an embodiment of the present invention has a decorative layer having a first principal surface and a second principal surface, the first principal surface having a concave-convex structure; a low refractive index layer provided on the first principal surface of the decorative layer; and a high refractive index layer provided on the side of the low refractive index layer opposite the decorative layer. [2] In the above [1], the low refractive index layer has a refractive index of 1.30 or less and a thickness of 0.3 μm or more. [3] In the above [1] or [2], the high refractive index layer has a refractive index of 1.60 to 2.20 and a thickness of 0.3 μm or more. [4] In any one of the above [1] to [3], the decorative layer has a function of changing the direction of light. [5] In any of the above [1] to [4], when the height of the projections and recesses in the projection-and-recess structure of the decorative layer is H and the pitch of the projections and recesses is P, P / H is 1.5 or more. [6] In any one of the above [1] to [5], the laminate film further has a colored layer on the opposite side of the high refractive index layer to the low refractive index layer. [7] According to another aspect of the present invention, there is provided an image display device having an image display surface and a back surface, and any one of the laminate films [1] to [6] above being disposed on the back surface. Effect of the Invention
[0006] According to an embodiment of the present invention, a laminate film can be provided that can realize a design with high brightness and reduced color unevenness. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic cross-sectional view of a laminated film according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a laminated film according to another embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic cross-sectional view illustrating a mode of use of the laminated film of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited to these embodiments. Note that, in order to make the drawings easy to see and understand, the drawings are drawn typically or conceptually, and the length, width, shape, size, ratio, direction, number, etc. may differ from the actual ones, and there may be no correspondence between the drawings.
[0009] A. Overall structure of laminated film FIG. 1 is a schematic cross-sectional view of a laminated film according to one embodiment of the present invention. The laminated film 100 in the illustrated example has a decorative layer 10, a low refractive index layer 20, and a high refractive index layer 30. The decorative layer 10 has a first main surface 10a and a second main surface 10b, and the first main surface 10a has an uneven structure. The low refractive index layer 20 is provided on the first main surface 10a of the decorative layer 10. The high refractive index layer 30 is provided on the side of the low refractive index layer 20 opposite to the decorative layer 10. By providing the low refractive index layer 20 and the high refractive index layer 30 in combination in such a positional relationship with respect to the decorative layer 10, a laminated film that can realize a design with high brightness and suppressed color unevenness can be obtained. In terms of the relationship between their thickness and the height (depth) of the uneven structure, the low refractive index layer 20 and the high refractive index layer 30 typically follow the uneven structure of the decorative layer 10 as shown in the illustrated example. On the other hand, either the low refractive index layer 20 or the high refractive index layer 30 may fill in the recesses of the uneven structure, making the side opposite the decorative layer a flat surface.
[0010] In the embodiment of the present invention, the decorative layer 10 typically has a function of changing the direction of light. The decorative layer 10 can express a design according to the purpose by controlling the uneven structure, for example, by controlling the transmission, reflection, diffraction, scattering, and diffusion of light in combination. A laminated film including such a decorative layer can achieve the following effects according to the type of decorative layer: (1) it can decorate the surface of various products and improve their design; (2) it can change the color of the surface of various products depending on the viewing angle; and (3) it can display different images, characters, etc. on the surface of various products depending on the viewing angle. Therefore, the laminated film according to the embodiment of the present invention can also be called a decorative film, an optical laminate, etc. The decorative layer 10 can express a design on one or both of the first main surface side and the second main surface side depending on the specific configuration. In one use form of the laminated film (described later), the decorative layer 10 can preferably express a design at least on the arrow side in FIG. 1. As the decorative layer, any appropriate configuration can be adopted as long as it has the above-mentioned functions. The specific configuration of the decorative layer will be described in Section B below.
[0011] The low refractive index layer 20 typically has a refractive index of 1.30 or less. By providing such a low refractive index layer at a predetermined position, appropriate reflection can be realized at the interface with the decorative layer. As a result, the reflectance of the laminated film can be increased, and therefore a design with high brightness can be expressed. The low refractive index layer 20 may be formed on the first main surface 10a of the decorative layer 10 via an adhesive layer, or may be formed directly on the first main surface. Preferably, the low refractive index layer is formed directly on the first main surface. With such a configuration, adverse effects caused by the refractive index of the adhesive layer can be avoided. Such direct formation can be achieved, for example, by coating or printing a low refractive index layer forming liquid as described later. Furthermore, the thickness of the low refractive index layer 20 is preferably 0.3 μm or more. If the thickness of the low refractive index layer is in such a range, the effect of the embodiment of the present invention can be more remarkable. Specifically, the hue change of the laminated film can be suppressed, and as a result, color unevenness of the expressed design can be suppressed. It can be presumed that this is because thin film interference between the low refractive index layer and the high refractive index layer is suppressed. The specific configuration of the low refractive index layer will be described in Section C below. The adhesive layer may be composed of a pressure-sensitive adhesive or an adhesive. The adhesive layer (or the adhesive or pressure-sensitive adhesive constituting it) may have a configuration well known in the industry, so a detailed description will be omitted. Unless otherwise specified below, the same applies to other "adhesive layers".
[0012] The high refractive index layer 30 typically has a refractive index of 1.60 to 2.20. By providing such a high refractive index layer at a predetermined position, a synergistic effect with the effect of providing the low refractive index layer can be achieved, resulting in a better reflection in the laminated film. As a result, a design having higher brightness than that of a low refractive index layer provided alone can be expressed. The high refractive index layer 30 may be formed on the low refractive index layer 20 via an adhesive layer, or may be formed directly on the low refractive index layer 20. Preferably, the high refractive index layer is formed directly on the low refractive index layer. With such a configuration, adverse effects due to the refractive index of the adhesive layer can be avoided. Such direct formation can be achieved, for example, by coating or printing a high refractive index layer forming liquid as described later. Furthermore, the thickness of the high refractive index layer 30 is preferably 0.3 μm or more. If the thickness of the high refractive index layer is in this range, the effect of the embodiment of the present invention can be more remarkable, as in the case where the thickness of the low refractive index layer is set to a predetermined value or more. Specifically, the hue change of the laminated film can be suppressed, and as a result, color unevenness of the displayed design can be suppressed. In one embodiment, the thickness of the high refractive index layer is greater than that of the low refractive index layer. In this case, the difference between the thickness of the high refractive index layer and the thickness of the low refractive index layer may be, for example, 0.2 μm to 3.0 μm, or may be, for example, 1.0 μm to 2.0 μm. The specific configuration of the high refractive index layer will be described in Section D below.
[0013] FIG. 2 is a schematic cross-sectional view of a laminated film according to another embodiment of the present invention. The laminated film 101 in the illustrated example further has a colored layer 40 on the side of the high refractive index layer 30 opposite to the low refractive index layer 20. By providing the colored layer 40, the design that appears by reflection can be made clearer. The colored layer 40 may be formed on the high refractive index layer 30 via an adhesive layer, or may be formed directly on the high refractive index layer 30. In the illustrated example, the colored layer 40 is formed on the high refractive index layer 30 via an adhesive layer 50. The adhesive layer in this embodiment may typically be a pressure-sensitive adhesive layer. The specific configuration of the colored layer will be described in Section E below.
[0014] If necessary, an adhesive layer (not shown) may be provided as the outermost layer on the high refractive index layer 30 side. By providing such an adhesive layer, the laminated film can be attached to an image display device. For practical purposes, it is preferable that a release liner (not shown) is temporarily attached to the laminated film until it is used. By temporarily attaching the release liner, the adhesive layer is protected and the laminated film can be formed into a roll.
[0015] The components of the laminated film will be described in detail below.
[0016] B. Decorative layer In the embodiment of the present invention, the decorative layer 10 has a function of changing the direction of light, as described above. Specific examples of the decorative layer include a shaping film, a reflective hologram film, a microlens array film, a prism film, and a lenticular lens. In addition, a reflective hologram film and the like may also be included in the shaping film, but in this specification, for convenience, the shaping film and the reflective hologram film and the like are described together.
[0017] The shaped film may have any suitable structure depending on the purpose. Examples of the uneven structure of the shaped film include a structure in which rectangular parallelepiped unevenness is arranged in a checkerboard pattern in plan view, a structure in which the recess has an inclined surface with different angles as shown in FIG. 1 (a vertical surface and an inclined surface in the illustrated example), a structure in which the recess is a quadrangular pyramid shape, a structure in which the recess is a truncated quadrangular pyramid shape, a structure in which the recess is a dome shape, an uneven shape having convex parts extending in one direction with a rectangular cross section at regular intervals (striped shape in plan view, so-called line & space), an uneven shape having convex parts extending in one direction with a corrugated cross section at regular intervals, an uneven shape having convex parts extending in one direction with a triangular cross section at regular intervals, and combinations thereof.
[0018] The shaped film can be produced by any suitable method. The shaped film can be produced, for example, by transferring the concave-convex structure of a mold to a resin sheet in a soft state. Examples of the soft resin sheet include a semi-cured thermosetting or active energy ray curable resin sheet and a thermoplastic resin sheet softened by heating. After the concave-convex structure is transferred to the thermosetting or active energy ray curable resin sheet, the sheet is cured by heating or by irradiating with active energy rays (typically visible light or ultraviolet light), and the concave-convex structure is fixed. After the concave-convex structure is transferred to the thermoplastic resin sheet, the sheet is solidified by cooling, and the concave-convex structure is fixed.
[0019] The reflection type hologram film may have any suitable configuration depending on the purpose. The reflection type hologram film may have any suitable fine uneven shape capable of exhibiting functions such as light diffusion, light scattering, light reflection, and light diffraction. Representative examples include a Fourier transform structure, a lenticular lens, a light diffraction pattern, and a moth-eye structure. In addition, the reflection type hologram film may have an uneven shape such as a hairline pattern, a matte pattern, a line pattern, and an interference pattern that does not have a light diffraction function but can exhibit a unique brilliance. In one embodiment, the reflection type hologram film may convert reflected light into diffracted light.
[0020] A microlens array film typically has a flat base portion and a lens portion provided on one surface of the base portion. The lens portion is composed of a plurality of lenses. The lenses constituting the lens portion are typically convex lenses, and may have, for example, a dome shape. The lenses may be provided in a matrix, in a predetermined pattern (for example, stripes), or randomly.
[0021] A prism film typically has a flat base portion and a prism portion. The prism portion typically includes an array of unit prisms that extend in one direction and have a triangular cross section that is convex on the side opposite to the base portion. The direction in which the unit prisms extend (the ridge direction of the unit prisms) can be appropriately set depending on the purpose.
[0022] A lenticular lens typically has a plurality of convex cylindrical lenses, each having a semicircular cross section, arranged in parallel (that is, in a stripe pattern).
[0023] In one embodiment, when the height of the unevenness in the uneven structure of the decorative layer 10 is H and the pitch of the unevenness is P, P / H is preferably 1.5 or more, more preferably 2.0 or more, even more preferably 3.0 or more, and particularly preferably 5.0 or more. On the other hand, P / H is preferably 100 or less, more preferably 70 or less, even more preferably 60 or less, and particularly preferably 50 or less. If the P / H of the uneven structure of the decorative layer is in such a range, the effect of the embodiment of the present invention can be more remarkable. If P / H is too small, the low refractive index layer may not be properly formed. The upper limit of P / H can be determined according to the desired design. In this specification, the "height of the unevenness" means the distance from the peak (or top) to the valley (or flat end) in one uneven portion, and when the unevenness is an irregular structure, it means the average distance from the peak (or top) to the valley (or flat end) in each uneven portion. In addition, the "pitch of the unevenness" means the distance from adjacent peaks (or crests) to adjacent peaks (or crests), and when the unevenness has an irregular structure, means the average distance from each adjacent peak (or crest) to each peak (or crest).
[0024] The pitch P of the irregularities and the height H of the irregularities can be appropriately set as long as the desired P / H is obtained. The pitch P is preferably 10 μm to 500 μm, more preferably 30 μm to 200 μm, and even more preferably 50 μm to 100 μm. The height H is preferably 0.1 μm to 100 μm, more preferably 1 μm to 50 μm, and even more preferably 2 μm to 20 μm.
[0025] The thickness of the decorative layer (the maximum thickness corresponding to the convex portions) is preferably 50 μm to 3 mm (3000 μm), and more preferably 100 μm to 1 mm (1000 μm).
[0026] C. Low refractive index layer The refractive index of the low refractive index layer 20 is typically 1.30 or less as described above, and the lower limit is more than 1.00. The refractive index of the low refractive index layer 20 is preferably 1.13 to 1.28, more preferably 1.14 to 1.27, even more preferably 1.15 to 1.26, and particularly preferably 1.16 to 1.25. If the refractive index of the low refractive index layer is in such a range, the deterioration of the function of the decorative layer caused by providing a layer on the first main surface (uneven surface) side of the decorative layer can be extremely well suppressed. The refractive index refers to a refractive index measured at a wavelength of 550 nm, unless otherwise specified. The refractive index is, for example, a value measured by the method described in the Examples below.
[0027] The total light transmittance of the low refractive index layer 20 is preferably 85% to 99%, more preferably 87% to 98%, and further preferably 89% to 97%. By providing such a low refractive index layer on the first main surface (uneven surface) side of the decorative layer, for example, it is possible to realize excellent transparency of the laminated film as a whole. As a result, for example, when the laminated film is applied to various products, it is possible to ensure the visibility of the design that can be expressed. The total light transmittance can be measured, for example, by a haze meter described later.
[0028] The haze of the low refractive index layer 20 is preferably less than 5%, more preferably less than 3%. On the other hand, the haze may be, for example, 0.1% or more, and may be 0.2% or more. By providing such a low refractive index layer on the first main surface (uneven surface) side of the decorative layer, for example, excellent transparency can be achieved for the entire laminated film. As a result, for example, when the laminated film is applied to various products, the visibility of the design that can be expressed can be ensured. For example, the haze can be calculated from the following formula using a value measured by a haze meter (for example, "HM-150" manufactured by Murakami Color Research Laboratory Co., Ltd.). Haze (%) = [Diffuse transmittance (%) / Total light transmittance (%)] x 100 (%)
[0029] The thickness of the low refractive index layer 20 is preferably 0.3 μm or more, more preferably 1.0 μm or more, even more preferably 1.2 μm or more, particularly preferably 1.5 μm or more, and particularly preferably 1.8 μm or more, as described above. The thickness of the low refractive index layer may be, for example, 2.2 μm or more, or may be, for example, 2.5 μm or more, or may be, for example, 2.8 μm or more. On the other hand, the thickness of the low refractive index layer may be, for example, 20 μm or less, or may be, for example, 10 μm or less, or may be, for example, 8 μm or less, or may be, for example, 5 μm or less. If the thickness of the low refractive index layer is in such a range, as described above, the hue change of the laminated film can be suppressed, and as a result, the color unevenness of the design that appears can be suppressed.
[0030] The low refractive index layer may have any suitable structure that can achieve the desired characteristics. For example, materials described in International Publication No. 2004 / 113966, JP 2013-254183 A, and JP 2012-189802 A may be used as materials for forming the low refractive index layer. Representative examples of materials for forming the low refractive index layer include silicon compounds. Examples of silicon compounds include silica-based compounds; hydrolyzable silanes, and their partial hydrolyzates and dehydration condensates; silicon compounds containing silanol groups; and activated silica obtained by contacting silicate with acid or ion exchange resin. Examples of materials for forming the low refractive index layer include organic polymers; polymerizable monomers (e.g., (meth)acrylic monomers and styrene monomers); and curable resins (e.g., (meth)acrylic resins, fluorine-containing resins, and urethane resins). These materials may be used alone or in combination of two or more.
[0031] In one embodiment, the low refractive index layer may contain spaces such as holes and gaps therein. In this case, the porosity of the low refractive index layer is preferably 20 volume % to 60 volume %, more preferably 25 volume % to 55 volume %, further preferably 30 volume % to 50 volume %, and particularly preferably 35 volume % to 45 volume %. With such a porosity, the refractive index of the low refractive index layer can be set in an appropriate range, and strength can be ensured. Here, the porosity is a value calculated from the refractive index measured by an ellipsometer using the Lorentz-Lorenz's formula.
[0032] The size of the pores that can be contained in the low refractive index layer can be adjusted to a desired size depending on the purpose and use. The size of the pores that can be contained in the low refractive index layer is, for example, 2 nm or more, preferably 5 nm or more, more preferably 10 nm or more, and even more preferably 20 nm or more. On the other hand, the size of the pores that can be contained in the low refractive index layer is, for example, 500 nm or less, preferably 200 nm or less, and more preferably 100 nm or less. The size of the pores refers to the diameter of the major axis of the pores among the diameter of the major axis and the diameter of the minor axis.
[0033] The size of the pores can be quantified by the BET test method. In one embodiment, 0.1 g of a measurement sample (for example, the formed low refractive index layer) is placed in the capillary of a specific surface area measurement device (for example, "ASAP2020" manufactured by Micromeritics), and then the measurement sample is dried under reduced pressure for 24 hours at room temperature to remove gas contained in the measurement sample. Then, an adsorption isotherm is drawn by adsorbing nitrogen gas to the measurement sample, and the pore distribution is obtained. This allows the size of the pores to be evaluated.
[0034] The low refractive index layer having a space therein includes, for example, a porous layer made of a porous body and / or a layer containing an air layer at least in a part thereof. The low refractive index layer typically contains aerogel and / or particles (which may be, for example, hollow fine particles and / or porous particles). The low refractive index layer is preferably a nanoporous layer (specifically, a layer in which the diameter of 90% or more of the pores is 10 -1 nm~10 3 The porous layer may be in the range of 1 nm.
[0035] Any suitable particle may be used as the particle. The particle is typically composed of a silica-based compound. Examples of particle shapes include spherical, plate-like, needle-like, string-like, and bunch-of-grapes shapes. Examples of string-like particles include particles in which a plurality of particles having a spherical, plate-like, or needle-like shape are linked together in a string-like shape, short fiber-like particles (for example, short fiber-like particles described in JP-A-2001-188104), and combinations thereof. The string-like particles may be linear or branched. Examples of bunch-of-grapes particles include particles in which a plurality of spherical, plate-like, and needle-like particles are aggregated to form a bunch-of-grapes shape. The shape of the particles can be confirmed, for example, by observation using a transmission electron microscope.
[0036] An example of the low refractive index layer is a structure composed of one or more types of structural units that form a fine void structure, and these structural units are bonded together (for example, chemically bonded via catalytic action). The shape of the structural unit can be, for example, a particulate, fibrous, rod-like, or flat plate-like shape. The structural unit may have only one shape, or may have two or more shapes in combination.
[0037] A specific example of the low refractive index layer is a porous layer composed of a porous body in which particles having micropores (hereinafter referred to as micropore particles) are chemically bonded to each other. Such a porous layer can be obtained, for example, by chemically bonding micropore particles to each other. The shape of the micropore particles is not particularly limited, and may be, for example, spherical or other shapes. In addition, the micropore particles may be, for example, sol-gel beaded particles, nanoparticles (for example, hollow nanosilica nanoballoon particles), nanofibers, etc. Representative micropore particles include inorganic substances. Specific examples of inorganic substances include silicon (Si), magnesium (Mg), aluminum (Al), titanium (Ti), zinc (Zn), and zirconium (Zr). These may be used alone or in combination of two or more. In one embodiment, the micropore particles are, for example, micropore particles of a silicon compound, and the porous body is, for example, a silicone porous body. The micropore particles of a silicon compound include, for example, a pulverized product of a gel-like silica compound.
[0038] Another example of the low refractive index layer is a layer containing a fibrous material such as nanofibers, and in which a space is formed by the entanglement of the fibrous material. Further examples of the low refractive index layer include a layer formed using hollow nanoparticles or nanoclay, and a layer formed using hollow nanoballoons or magnesium fluoride. The low refractive index layer may be composed of a single constituent material or a plurality of constituent materials. The low refractive index layer may be composed of a single form of the above examples, or a plurality of forms of the above examples.
[0039] The porous layer may be, for example, an open-cell structure in which the pore structure is continuous. The open-cell structure means that the pore structure is three-dimensionally connected in a porous body (for example, a silicone porous body), and can also be said to be a state in which the spaces of the pore structure are continuous. The open-cell structure of the porous layer can increase the porosity. It is difficult to form an open-cell structure using closed-cell particles having individual pore structures such as hollow particles (for example, hollow silica). However, when silica sol particles (pulverized gel-like silicon compound forming a sol) are used, for example, the silica sol particles can have a three-dimensional dendritic structure, so that the dendritic particles can be precipitated and deposited in the coating film (coated film of sol containing pulverized gel-like silicon compound) to easily form an open-cell structure. The porous layer preferably has a monolith structure in which the open-cell structure includes a plurality of pore distributions. The monolith structure means, for example, a hierarchical structure including a structure in which nano-sized fine pores exist and an open-cell structure in which nano-sized fine pores are aggregated. The monolithic structure, for example, can provide film strength through fine pores while providing high porosity through a coarse open-cell structure, thereby achieving both film strength and high porosity.
[0040] For example, the monolith structure can be formed by controlling the pore distribution of the void structure generated in the gel (gel silicon compound) before pulverizing into silica sol particles. Also, for example, when pulverizing the gel silicon compound, the particle size distribution of the silica sol particles after pulverization can be controlled to a predetermined size, thereby forming a monolith structure. Note that the particle size distribution can be measured by, for example, a particle size distribution evaluation device such as dynamic light scattering method or laser diffraction method, and an electron microscope such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).
[0041] As described above, the porous layer may contain pulverized gel compounds such as gel silicon compounds, and the pulverized particles are chemically bonded to each other. The chemical bond is not particularly limited, and may be, for example, a cross-linked bond, a covalent bond, or a hydrogen bond. The volume average particle size of the pulverized particles in the porous layer is, for example, 0.10 μm or more, preferably 0.20 μm or more, and more preferably 0.40 μm or more. On the other hand, the volume average particle size of the pulverized particles in the porous layer is, for example, 2.00 μm or less, preferably 1.50 μm or less, and more preferably 1.00 μm or less. The volume average particle size is an index of the particle size variation of the pulverized particles, and is determined by particle size distribution measurement.
[0042] The low refractive index layer may contain silicon atoms. For example, the silicon atoms contained in the low refractive index layer are preferably siloxane bonded. The ratio of unbonded silicon atoms (specifically, residual silanol) among all silicon atoms contained in the low refractive index layer is, for example, less than 50%, preferably 30% or less, more preferably 15% or less.
[0043] The low refractive index layer can be formed, for example, by coating or printing a low refractive index layer forming liquid (sometimes also referred to as a coating liquid) on the first main surface (uneven surface) of the decorative layer. More specifically, the low refractive index layer can be formed by heating a coating film or a printed layer of the low refractive index layer forming liquid formed on the first main surface (uneven surface) of the decorative layer.
[0044] In one embodiment, the coating film can be formed using a coating liquid containing microporous particles, and the microporous particles can be chemically bonded to each other by heating (including drying) this coating liquid. The coating liquid containing microporous particles is, for example, a suspension. For example, a catalyst (crosslinking reaction promoter) that promotes crosslinking between microporous particles (for example, a dehydration condensation reaction of residual silanol groups that may be contained in the microporous particles) and / or a substance (catalyst generator) that generates a catalyst (crosslinking reaction promoter) may be added to the coating liquid. Examples of the catalyst include photoactive catalysts and thermally active catalysts. Examples of the substance (catalyst generator) that generates a catalyst include photocatalyst generators and thermal catalyst generators. Examples of the photocatalyst generator include photobase generators (catalysts that generate a basic catalyst by light irradiation) and photoacid generators (substances that generate an acidic catalyst by light irradiation). For example, the microporous particles are pulverized products of a gel-like compound (preferably, a gel-like silicon compound), and the low refractive index layer is a porous layer composed of a porous body (preferably, a silicone porous body) containing the pulverized product of the gel-like compound. Such microporous particles may have a state in which the three-dimensional structure of the gel-like compound before pulverization is dispersed in the three-dimensional basic structure, and a structure based on the three-dimensional basic structure may be formed by using such microporous particles. Specifically, a new structure different from the three-dimensional structure of the gel-like compound may be formed. In this way, the finally obtained low refractive index layer (porous layer) may have a low refractive index similar to that of an air layer, for example. In addition, by chemically bonding the microporous particles to each other, the above-mentioned three-dimensional basic structure may be fixed, and sufficient strength may be ensured in the finally obtained low refractive index layer (porous layer). The specific configuration and details of the formation method of the low refractive index layer (porous layer) are described, for example, in International Publication No. 2019 / 151073. The description of the publication is incorporated herein by reference.
[0045] The coating thickness of the coating liquid can be set according to the thickness desired for the low refractive index layer. The heating temperature of the coating film (coating liquid) is, for example, 20° C. or higher, preferably 50° C. or higher. Meanwhile, the heating temperature of the coating film (coating liquid) is, for example, 200° C. or lower, preferably 150° C. or lower. The heating time of the coating film (coating liquid) is, for example, 10 seconds or longer. Meanwhile, the heating time of the coating film (coating liquid) is, for example, 24 hours or shorter, preferably 1 hour or shorter, more preferably 30 minutes or shorter, and even more preferably 10 minutes or shorter.
[0046] D. High refractive index layer The refractive index of the high refractive index layer 30 is typically 1.60 to 2.20 as described above. The refractive index of the high refractive index layer 30 is preferably 1.62 to 2.00, more preferably 1.63 to 1.90, even more preferably 1.65 to 1.85, and particularly preferably 1.67 to 1.80. If the refractive index of the high refractive index layer is in such a range, even better reflection can be achieved in the laminated film. As a result, a design with extremely high brightness can be expressed.
[0047] The total light transmittance of the high refractive index layer 30 is preferably 85% to 99%, more preferably 87% to 98%, and further preferably 89% to 97%. If the total light transmittance of the high refractive index layer is within such a range, for example, when the laminate film is applied to various products, the visibility of the design that can be expressed can be ensured well.
[0048] The haze of the high refractive index layer 30 is preferably less than 2%, more preferably less than 1.5%. On the other hand, the haze may be, for example, 0.1% or more, or 0.2% or more. If the haze of the high refractive index layer is in this range, for example, when the laminate film is applied to various products, the visibility of the design that can be expressed can be ensured well.
[0049] The thickness of the high refractive index layer 30 is preferably 0.3 μm or more, more preferably 1.0 μm or more, even more preferably 1.2 μm or more, particularly preferably 1.5 μm or more, and particularly preferably 1.8 μm or more, as described above. The thickness of the high refractive index layer may be, for example, 3.0 μm or more, or may be, for example, 3.5 μm or more, or may be, for example, 4.0 μm or more. On the other hand, the thickness of the high refractive index layer may be, for example, 20 μm or less, or may be, for example, 12 μm or less, or may be, for example, 10 μm or less, or may be, for example, 7 μm or less. If the thickness of the high refractive index layer is in such a range, as described above, the hue change of the laminated film can be suppressed, and as a result, the color unevenness of the design that appears can be suppressed.
[0050] As the high refractive index layer 30, any appropriate configuration may be adopted as long as the above-mentioned characteristics are satisfied. The high refractive index layer typically includes a binder resin (matrix) and a refractive index adjusting material. As the binder resin, any appropriate resin may be used. A water-soluble resin is preferable. Representative examples of the water-soluble resin include polyvinyl alcohol (PVA)-based resin and water-soluble acrylic resin. A PVA-based resin is preferable. As the PVA-based resin, any appropriate resin may be adopted. For example, polyvinyl alcohol and ethylene-vinyl alcohol copolymer are included. Polyvinyl alcohol is obtained by saponifying polyvinyl acetate. An ethylene-vinyl alcohol copolymer is obtained by saponifying an ethylene-vinyl acetate copolymer.
[0051] The saponification degree of the PVA resin is preferably 93.5 mol% or more, more preferably 95.0 mol% or more, and even more preferably 99.0 mol% or more. The upper limit of the saponification degree may be, for example, 100 mol%, or may be, for example, 99.95 mol%, or may be, for example, 99.93 mol%. By using a PVA resin with such a saponification degree, a high refractive index layer with excellent durability can be obtained.
[0052] The weight average molecular weight of the PVA resin can be appropriately selected depending on the purpose. The weight average molecular weight is preferably 20,000 to 110,000, more preferably 30,000 to 100,000, and further preferably 40,000 to 80,000. The weight average molecular weight can be measured by, for example, gel permeation chromatography (GPC).
[0053] The refractive index adjusting material is used to substantially increase the refractive index of the layer to be formed. Therefore, the refractive index adjusting material is typically a high refractive index material, and may have a refractive index of, for example, 2.30 or more. As the refractive index adjusting material, any appropriate configuration may be adopted as long as it has such a refractive index. Representative examples of the refractive index adjusting material include metal oxide fine particles. Specific examples of metal oxides include titanium oxide (TiO2), silica (SiO2), zirconium oxide (ZrO2), cerium oxide (CeO2), tin oxide (SnO2), iron oxide (Fe2O3, Fe3O4), zinc oxide (ZnO), antimony tin oxide (ATO), indium tin oxide (ITO), phosphorus tin compound (PTO), antimony oxide (Sb2O5), aluminum zinc oxide (AZO), gallium zinc oxide (GZO), and zinc antimonate (ZnSb2O6). The metal oxide fine particles may be used alone or in combination of two or more kinds.
[0054] The average particle diameter of the high refractive index fine particles is preferably 1 nm to 100 nm, more preferably 2 nm to 50 nm, and further preferably 5 nm to 20 nm. Such an average particle diameter provides excellent transparency and easy handling. The average particle diameter is a value measured without distinguishing between primary particles and secondary particles, regarding secondary particles as one particle. The average particle diameter can be determined, for example, by observing a predetermined region of the cross section of the high refractive index layer with a transmission electron microscope and averaging the particle diameters of particles (for example, 50 particles) observed in the region.
[0055] The content of the high refractive index fine particles in the high refractive index layer may be, for example, 40 parts by weight to 300 parts by weight, and is, for example, 70 parts by weight to 150 parts by weight, relative to 100 parts by weight of the binder resin.
[0056] E. Colored layer The colored layer 50 may be a monochromatic layer or a design layer having a predetermined design. The colored layer is preferably a monochromatic layer, more preferably a black monochromatic layer. With such a configuration, the design that appears by reflection in the laminated film can be made clearer.
[0057] The colored layer typically contains a binder resin (matrix) and a colorant. Examples of the binder resin include chlorinated polyolefin (e.g., chlorinated polyethylene, chlorinated polypropylene), polyester resin, urethane resin, acrylic resin, vinyl acetate resin, vinyl chloride-vinyl acetate copolymer, and cellulose resin. The binder resin may be used alone or in combination of two or more. In one embodiment, the binder resin is a thermally polymerizable resin. Since the thermally polymerizable resin requires less use than the photopolymerizable resin, the amount of the colorant used (the colorant content in the colored layer) can be increased. As a result, particularly when forming a black colored layer, a colored layer having a very small total light transmittance and excellent concealing properties can be formed. In one embodiment, the binder resin is an acrylic resin, preferably an acrylic resin containing a polyfunctional monomer (e.g., pentaerythritol triacrylate) as a copolymerization component. By using an acrylic resin containing a polyfunctional monomer as a copolymerization component, a colored layer having an appropriate elastic modulus can be formed.
[0058] As the colorant, any suitable colorant can be used depending on the purpose. Specific examples of the colorant include inorganic pigments such as titanium white, zinc white, carbon black, iron black, red oxide, chrome vermilion, ultramarine blue, cobalt blue, yellow lead, and titanium yellow; organic pigments or dyes such as phthalocyanine blue, indanthrene blue, isoindolinone yellow, benzidine yellow, quinacridone red, polyazo red, perylene red, and aniline black; metal pigments made of scaly foil such as aluminum and brass; and pearlescent pigments (pearl pigments) made of scaly foil such as titanium dioxide-coated mica and basic lead carbonate. When forming a black colored layer, carbon black, iron black, and aniline black are preferably used. In this case, it is preferable to use the colorants in combination. This is because they absorb visible light widely and evenly and can form a colored layer that is not colored (i.e., completely black). For example, in addition to the above colorants, azo compounds and / or quinone compounds can be used. In one embodiment, the colorant contains carbon black as a main component and other colorants (e.g., an azo compound and / or a quinone compound). With this configuration, a colored layer that is free of coloring and has excellent stability over time can be formed. When forming a black colored layer, the colorant can be used in a ratio of preferably 50 parts by weight to 200 parts by weight per 100 parts by weight of the binder resin. In this case, the content of carbon black in the colorant is preferably 80% to 100%. By using the colorant (particularly carbon black) in such a ratio, a colored layer that has a very small total light transmittance and excellent stability over time can be formed.
[0059] The thickness of the colored layer may be, for example, 1 μm to 3 mm (3000 μm), or may be, for example, 10 μm to 1 mm (1000 μm). Furthermore, the colored layer has a total light transmittance of preferably 0.01% or less at a thickness of 100 μm, more preferably 0.008% or less. If the total light transmittance is in this range, the design expressed by reflection in the laminated film can be made exceptionally clear.
[0060] F. Image display device The laminate film according to the embodiment of the present invention is used in an image display device. Therefore, such an image display device can also be included in the embodiment of the present invention. Representative examples of the image display device include a liquid crystal display device and an electroluminescence (EL) display device (e.g., an organic EL display device and an inorganic EL display device). Examples of the product form of the image display device include a smartphone and a tablet terminal. The laminate film according to the embodiment of the present invention may also be used in a cover case that houses the image display device.
[0061] FIG. 3 is a schematic cross-sectional view for explaining an image display device according to one embodiment of the present invention (in other words, a usage form of the laminated film in FIG. 1). The image display device 200 in the illustrated example has an image display surface 201 and a back surface (a surface not involved in image display) 202. The laminated film 100 in FIG. 1 is disposed on the back surface 202 of the image display device 200. More specifically, the laminated film 100 is attached to the back surface 202 of the image display device 200 via the adhesive layer 120 so that the high refractive index layer 30 faces the image display device 200. According to such an embodiment, a design is expressed on the back surface of the image display device by the laminated film, and the image display device itself can be given a design. According to such an embodiment, for example, when a case is not used for a smartphone, the commercial value of the smartphone can be increased. As is clear from FIG. 3, the design by the laminated film is expressed on the back surface 202 of the image display device 200 as indicated by the arrow, and is not involved in image display.
[0062] FIG. 3 illustrates an embodiment in which the laminate film of FIG. 1 is disposed in an image display device, but it goes without saying that laminate films according to other embodiments of the present invention (e.g., the laminate film of FIG. 2, laminate films according to embodiments not shown) may also be disposed in an image display device. EXAMPLES
[0063] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring each property are as follows. In addition, "%" and "parts" in the examples are based on weight, unless otherwise specified.
[0064] (1) Refractive index The low refractive index layer or high refractive index layer used in the examples and comparative examples was formed on an acrylic film. The obtained laminate was cut to a size of 25 mm x 50 mm. The cut laminate was attached to the surface of a glass plate (thickness: 3 mm) via an adhesive. The center of the back surface of the glass plate (diameter: about 20 mm) was filled with black marker to prepare a sample that was not reflective on the back surface of the glass plate. The sample was set in an ellipsometer (JA Woollam Japan: VASE) and the refractive index was measured under conditions of a wavelength of 550 nm and an incident angle of 50 to 80 degrees.
[0065] (2) Thickness The thickness was measured using an interference film thickness meter (Otsuka Electronics Co., Ltd., product name "MCPD-3000").
[0066] (3)Reflectance For the laminate films obtained in the examples and comparative examples, the spectral reflectance in the visible light region was determined using a spectrophotometer (manufactured by Hitachi High-Technologies Corporation, product name "U4100") and evaluated according to the following criteria. ○ (Good): Reflectance is 5.0% or more × (Poor): Reflectance is less than 5.0%
[0067] (4) Hue change The chromaticity value (x, y) was calculated from the spectral reflectance obtained in (3) above. The change Δxy from the achromatic value (x', y') was calculated using the following formula: Δxy={(xx´) 2 +(yy´) 2} 1 / 2 The obtained Δxy was evaluated as an index of the hue change according to the following criteria. ◎(Excellent) :Δxy(×10 2 ) is less than 3.0 ○(Good) :Δxy(×10 2 ) is 3.0 or more and less than 5.0 △(Acceptable): Δxy(×10 2 ) is 5.0 or more and less than 7.0
[0068] [Production Example 1] Preparation of coating liquid for forming low refractive index layer (1) Gelation of silicon compounds 0.95 g of methyltrimethoxysilane (MTMS), a precursor of a silicon compound, was dissolved in 2.2 g of dimethyl sulfoxide (DMSO) to prepare mixed solution A. 0.5 g of 0.01 mol / L oxalic acid solution was added to this mixed solution A and stirred at room temperature for 30 minutes to hydrolyze MTMS, producing mixed solution B containing tris(hydroxy)methylsilane. To 5.5 g of DMSO, 0.38 g of 28 wt % ammonia water and 0.2 g of pure water were added, and then the above mixed solution B was further added and stirred at room temperature for 15 minutes to gel tris(hydroxy)methylsilane, thereby obtaining mixed solution C containing a gel-like silicon compound. (2) Aging treatment The mixed solution C containing the gel-like silicon compound prepared as above was incubated as it was at 40° C. for 20 hours for aging treatment. (3) Crushing Next, the gel-like silicon compound aged as described above was crushed into granules of several mm to several cm in size using a spatula. Next, 40 g of isopropyl alcohol (IPA) was added to the mixed liquid C, and after light stirring, the mixture was left to stand at room temperature for 6 hours, and the solvent and catalyst in the gel were decanted. The same decantation process was performed three times to replace the solvent, and a mixed liquid D was obtained. Next, the gel-like silicon compound in the mixed liquid D was crushed (high-pressure media-less crushing). The crushing process (high-pressure media-less crushing) was performed using a homogenizer (manufactured by SMT Co., Ltd., product name "UH-50"), and 1.85 g of the gel-like compound and 1.15 g of IPA in the mixed liquid D were weighed into a 5 cc screw bottle, and then crushed for 2 minutes under the conditions of 50 W and 20 kHz. The gel-like silicon compound in the mixed solution D was pulverized by this pulverization process, and the mixed solution D became a pulverized sol solution E. The volume average particle size indicating the particle size variation of the pulverized material contained in the sol solution E was confirmed by a dynamic light scattering nanotrack particle size analyzer (manufactured by Nikkiso Co., Ltd., UPA-EX150 type) and was 0.50 to 0.70 μm. Furthermore, 0.015 g of a 1.5 wt % MEK (methyl ethyl ketone) solution of a photobase generator (Wako Pure Chemical Industries, Ltd., product name: WPBG266) and 0.005 g of a 5% MEK solution of a bis-crosslinking accelerator ((trimethoxysilyl)hexane) were added to 0.75 g of the sol solution E to obtain a coating solution 1 for forming a low refractive index layer. The refractive index of the low refractive index layer formed using this coating solution was 1.16.
[0069] [Production Example 2] Preparation of coating liquid for forming low refractive index layer A coating solution 2 for forming a low refractive index layer was obtained in the same manner as in Production Example 1, except that 0.060 g of a 1.5 wt % MEK (methyl ethyl ketone) solution of a base generator (Wako Pure Chemical Industries, Ltd., product name: WPBG266) and 0.018 g of a 5% MEK solution of a bis-crosslinking accelerator ((trimethoxysilyl)hexane) were added to 0.75 g of sol solution E. The refractive index of the low refractive index layer formed using this coating solution was 1.19.
[0070] [Production Example 3] Preparation of coating liquid for forming low refractive index layer A coating solution 3 for forming a low refractive index layer was obtained in the same manner as in Production Example 1, except that 0.180 g of a 1.5 wt % MEK (methyl ethyl ketone) solution of a base generator (Wako Pure Chemical Industries, Ltd., product name: WPBG266) and 0.054 g of a 5% MEK solution of a bis-crosslinking accelerator ((trimethoxysilyl)hexane) were added to 0.75 g of sol solution E. The refractive index of the low refractive index layer formed using this coating solution was 1.25.
[0071] [Production Example 4] Preparation of coating liquid for forming high refractive index layer A 6.0% aqueous solution of polyvinyl alcohol (manufactured by Japan Vinyl Acetate & Poval, product name "JC-25") was prepared. 72 parts (solids) of titanium oxide sol (manufactured by Taki Chemical Industry, product name "M-6": average particle size of titanium oxide 5 nm) was added to 100 parts (solids) of this aqueous solution to obtain coating solution A for forming a high refractive index layer. The refractive index of the high refractive index layer formed using this coating solution was 1.65.
[0072] [Production Example 5] Preparation of coating liquid for forming high refractive index layer Except for adding 130 parts (solid content) of titanium oxide sol to 100 parts (solid content) of the PVA aqueous solution, the same procedure as in Production Example 4 was followed to obtain a coating solution B for forming a high refractive index layer. The refractive index of the high refractive index layer formed using this coating solution was 1.70.
[0073] [Production Example 6] Preparation of coating liquid for forming high refractive index layer Except for adding 240 parts (solid content) of titanium oxide sol to 100 parts (solid content) of the PVA aqueous solution, the same procedure as in Production Example 4 was followed to obtain a coating solution C for forming a high refractive index layer. The refractive index of the high refractive index layer formed using this coating solution was 1.75.
[0074] [Example 1] An acrylic film having an uneven structure on one side was used as the decorative layer. The coating liquid 1 for forming a low refractive index layer prepared in Production Example 1 was applied to the uneven surface of the acrylic film. The coating film was treated at a temperature of 100°C for 1 minute and dried to form a low refractive index layer (thickness 3.0 μm) on the uneven surface of the acrylic film. The refractive index of the low refractive index layer was 1.16 as described above. Next, the coating liquid B for forming a high refractive index layer prepared in Production Example 5 was applied to the surface of the low refractive index layer. The coating film was treated at a temperature of 100°C for 3 minutes and dried to form a high refractive index layer (thickness 4.5 μm) on the low refractive index layer. The refractive index of the high refractive index layer was 1.70 as described above. In this way, a laminated film having a configuration of a decorative layer / a low refractive index layer / a high refractive index layer was obtained. The obtained laminated film was subjected to the evaluation of the above-mentioned "reflectance" and "hue change". The results are shown in Table 1.
[0075] [Examples 2 to 8] A laminate film was obtained in the same manner as in Example 1, except that the types and coating thicknesses of the low refractive index layer-forming coating liquid and the high refractive index layer-forming coating liquid were changed to form low refractive index layers and high refractive index layers having the refractive indices and thicknesses shown in Table 1. The obtained laminate film was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0076] [Comparative Example 1] The acrylic film used in Example 1 was directly subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0077] [Comparative Example 2] Except for not forming the high refractive index layer, a laminate film having a decorative layer / low refractive index layer structure was obtained in the same manner as in Example 2. The obtained laminate film was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0078] [Table 1]
[0079] As is clear from Table 1, according to the examples of the present invention, a laminate film having high reflectance and suppressed hue change can be obtained. Such a laminate film can realize a design having high brightness and suppressed color unevenness. [Industrial Applicability]
[0080] The laminate film according to the embodiment of the present invention can be suitably used as a decorative film, and in particular, can be suitably used as a decorative film applied to the back surface (surface not involved in image display) of an image display device. [Explanation of symbols]
[0081] 10 Decorative layer 10a First main surface 10b Second main surface 20 Low refractive index layer 30 High refractive index layer 100 Laminated Film 120 Adhesive layer 200 Image display device
Claims
1. a decorative layer having a first main surface and a second main surface, the first main surface having a concave-convex structure; a low refractive index layer provided on a first main surface of the decorative layer; a high refractive index layer provided on the opposite side of the low refractive index layer to the decorative layer; having Laminated film.
2. 2. The laminate film according to claim 1, wherein the low refractive index layer has a refractive index of 1.30 or less and a thickness of 0.3 μm or more.
3. 3. The laminated film according to claim 2, wherein the high refractive index layer has a refractive index of 1.60 to 2.20 and a thickness of 0.3 μm or more.
4. The laminated film according to claim 1 , wherein the decorative layer has a function of changing the direction of light.
5. 2. The laminated film according to claim 1, wherein when the height of the projections and recesses in the projection-and-recess structure of the decorative layer is H and the pitch of the projections and recesses is P, P / H is 1.5 or more.
6. The laminate film according to claim 1 , further comprising a colored layer on the opposite side of the high refractive index layer to the low refractive index layer.
7. A display device having an image display surface and a back surface, The laminate film according to any one of claims 1 to 5 is disposed on the back surface. Image display device.
8. A display device having an image display surface and a back surface, The laminate film according to claim 6 is disposed on the back surface. Image display device.
Citation Information
Patent Citations
Decorative sheet, decorative molded article, and manufacturing method of decorative molded article
JP2017047594A
Hologram structure, cover member with hologram, product, method of manufacturing cover member with hologram and supply reel
JP2022057471A
